A wireless-sensor-networks-based localisation systems for tracking positions in an indoor environments - Chang, Wai Kwong. (2011)
In this project, the author aim to develop localization and tracking system which can be used in an indoor environment. Accurate indoor localization has long been an objective of the ubiquitous computing research community, and numerous indoor localization solutions based on 802.11, Bluetooth, ultrasound and infrared technologies have been proposed. This project aims to develop indoor localization system based on wireless sensor networks (WSN), which are portable and energy efficient. The system will work on extrapolating distance from RSSI (Received Signal Strength Indicator) of the transmitted signals, and then implementing localization algorithms to track the location history.